Interface Oral Health Science 2007 Proceedings of the 2nd International Symposium for Interface Oral Health Science, Held in Sendai, Japan, Between 18 and 19 February, 2007 - Watanabe, M.; Okuno, O.; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2007)
Since 2002, the Tohoku University Graduate School of Dentistry has proposed “Interface Oral Health Science” as a major theme for next-generation dental research. That theme is based on the innovative concept that healthy oral function is provided by biological and biomechanical harmony among three systems: (1) oral tissues including the teeth, mucosa, bones, and muscles (host); (2) parasitic microorganisms of the oral cavity (parasites); and (3) biomaterials. The concept posits that oral diseases such as dental caries, periodontal disease, and tempo- mandibular disorders should be interpreted as interface diseases that result from disruption of the intact interfaces among these systems. The uniqueness of this concept rests on the fact that it not only encompasses the entire ? eld of dentistry and dental care, but also expands the common ground shared with many other ? elds, including medicine, pharmaceutical science, agriculture, material science, and engineering. Our Graduate School of Dentistry aims to promote advances in dental research and to activate interdisciplinary research with related ? elds by putting interface oral health science into practice. On this basis we organized the First International Symposium for Interface Oral Health in February 2005, with productive discussions stimulated by two special lectures, three symposia, and poster presentations. A monograph titled Interface Oral Health Science that s- marized the contents of the symposium was published in the autumn of 2005 (International Congress Series 1284, Elsevier, Amsterdam). The Second International Symposium was the most recent.
Plenary lectures -- Host—parasite interface, from oral biofilm to host response in oral mucosa -- Biomaterials: Novel dental biomaterials -- Biomaterials: Scaffolds for oral tissue regeneration -- Biomechanical-biological interface -- Host-parasite interface -- Biomaterial interface.
Keywords: Dentistry; Biomaterials; Dentistry; Biomaterials